The Socio-Economic Condition of the Construction Workers of Dhaka City: An Empirical Study - Biswas, Buddha Dev; Islam, Md. Jahirul (AIUB Journal of Business and Economics, 2018)
This paper explores the socio-economic condition of the construction workers from Azimpur area in Dhaka city. This study is quantitative in nature. A theoretical framework has been made in this study. Push & Pull Factors and Neoclassical Economic Theory have great relations with the existing research. The study shows that all construction workers are migrants who have migrated from the rural areas to Dhaka city to get jobs. They migrated to Dhaka city because of Push & Pull factors. Though Bangladesh is a densely populated country, the capital is not sufficient for incorporating the rural people in job avenues. Even though some people earn in rural areas, it is insufficient for them. All of these situations have forced the rural people to migrate to Dhaka. Their uneducated status forces them to choose the occupation of daily laborers —regardless of being male and female. The female laborers usually get fewer wages than the male laborers. Besides, both the male and the female laborers are cheated by the employers or the middlemen. The laborers have no fixed wage. They fix it by bargaining with the employers. This study explores the socio-economic situation of this community who work as construction workers through an in-depth investigation.